Towards becoming a transnational language educator - Natalia Wright (Australian Journal of Applied Linguistics)
The issues surrounding the personal and professional lives of TESOL educators in transnational landscapes have gained increased attention in the past decade. Existing research on transnationalism underscores the significance of expatriates’ experiences, particularly those who originate from ‘non-center’ and whose careers lead them to work in ‘periphery’ countries, setting their experiences apart from those of (im)migrants. This study examines the experiences of ‘non-native’ English-speaking (NNEST) teachers working in transnational contexts, their motivations for relocation, and the challenges they face in adapting to new societies. Guided by the concept of ‘becoming’, the research investigates the key turning points and types of becomings encountered by these expatriate teachers in their journeys towards a transnational identity. Drawing on theories of the ‘Third Space’, the article attempts to understand the ideological transformations that occur within transnational spaces. The findings offer insights into the complex and evolving process of becoming transnational for expatriate ‘non-native’ language educators. By understanding their journeys of self-transformation, this study contributes to the literature on transnationalism and offers valuable perspectives for policymakers and educational bodies. The outcomes of this study endeavor to enhance support for NNESTs by recognizing their transnational experiences as pedagogical resources.